2020
DOI: 10.1017/ice.2020.427
|View full text |Cite
|
Sign up to set email alerts
|

Impact of national guidelines for antimicrobial stewardship to reduce antibiotic use in upper respiratory tract infection and gastroenteritis

Abstract: Objective: To examine whether the issue and dissemination of national guidelines in the Manual of Antimicrobial Stewardship had an impact on reducing antibiotic use for acute respiratory tract infection (ARTI) and gastroenteritis. Method: An interrupted time-series analysis was performed using a large nationwide database from June 2016 to June 2018. Outpatients with ARTI or gastroenteritis aged ≥6 years were identified. The outcome measures were any antibiotic use and broad-spectrum anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…However, a nationwide database study revealed that the national guidelines appeared to have no significant impact on antimicrobial use in outpatient care. 10 In the present study, we were unable to assess the length of the APD or changes in prescriptions after the results of cultures done in the emergency department became available because most patients received an antimicrobial prescription for only a few days before receiving follow up from their primary care provider. The relationship between prescribers’ individual level, training year, and subspecialty on interventions was not statistically accessed because of insufficient prescriber variables.…”
Section: Discussionmentioning
confidence: 87%
“…However, a nationwide database study revealed that the national guidelines appeared to have no significant impact on antimicrobial use in outpatient care. 10 In the present study, we were unable to assess the length of the APD or changes in prescriptions after the results of cultures done in the emergency department became available because most patients received an antimicrobial prescription for only a few days before receiving follow up from their primary care provider. The relationship between prescribers’ individual level, training year, and subspecialty on interventions was not statistically accessed because of insufficient prescriber variables.…”
Section: Discussionmentioning
confidence: 87%
“…This will decrease patient antibiotic expectation. Although some studies show no evidence,37 facility-specific guidelines and algorithms, adapted from national standard treatment guidelines, should be established with respect to properly diagnosing and treating URTIs 38–40…”
Section: Discussionmentioning
confidence: 99%
“…The third factor is the lack of evidence on physicians’ standard of care for the treatment of common cold. In Japan, despite the publication of national guidelines in 2016 regarding the appropriate use of antimicrobials, there was no significant change in the trend of antimicrobial use among outpatients with acute upper respiratory tract infection before and after the publication [ 39 ]. In this study, the percentage of antimicrobials in prescriptions (83%) was higher than that reported in previous studies (60%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%